The modern management accounting methods and their relationship to achieving the competitive advantage of business organizations: A field study of the industrial sector in Hafar Al-Batin (2020-2025) - Elhag, Noureldaim Eltayeb Yousif (Journal of Economic, Administrative and Legal Sciences, 2025)
The study addressed modern management accounting techniques and their relationship to achieving competitive advantage for business organizations in the industrial sector of Hafar Al-Batin. The aim was to examine the relationship between the application of modern management accounting techniques and the realization of competitive advantage in these organizations. The significance of the study lies in its potential contribution to the effective application of modern management accounting techniques in enhancing competitive advantage within the industrial sector. The study employed a descriptive-analytical methodology and utilized SPSS software to analyze data collected through a questionnaire distributed to a simple random sample of 104 participants from the study population.The findings revealed several key results, most notably the importance of applying modern management accounting techniques to achieve competitive advantage, with a mean score of (4.28 out of 5.00) with a standard deviation of (0.731), Industrial sector companies in Hafar Al-Batin employ target costing, total quality management, and just-in-time production, while they do not adopt activity-based costing (ABC) or the balanced scorecard (BSC). Furthermore, the study demonstrated a direct positive correlation (0.70) between modern management accounting techniques and the achievement of competitive advantage in these companies.The study recommended that industrial sector companies in Hafar Al-Batin adopt activity-based costing (ABC) and the balanced scorecard (BSC), raise awareness and provide training for accountants regarding their importance, and appoint specialized cost or management accountants alongside financial accountants. It further emphasized the need to develop accounting systems that support the implementation of modern management accounting techniques.
Keywords: Modern management accounting methods; Achieving competitive advantage; Business organizations; Industrial sector; Hafar Al-Batin